Musical Careers in Constant Crises: An Asynchronous Dialogue from Tehran to Athens, via Belfast and Vienna - Bastani, Hadi; Linardou, Anna; Sharafi, Rojin; Tsioulakis, Ioannis (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
COVID-19 has caused an unprecedented crisis for performing musicians globally. But how are these new circumstances perceived by musicians in localities that have gone through multiple crises in the recent past? This article unfolds as a dialogue between two academics and two musicians from Greece and Iran, touching on issues of precarity, creativity, capitalism, state support and control, and radical ideas for a post-COVID cultural economy. Reflecting on conditions of economic crisis (Greece) and sanctions and military tensions (Iran), we argue that a return to ‘normalcy’ post-COVID is neither feasible nor desired by most musicians outside of institutional elites. By examining the experiences of musicians in the periphery of global markets and artistic circulation, we enrich the analysis of these unprecedented circumstances, but also find well-established coping strategies and seeds of resistance.